Leucocyte Rheological Properties Are Altered in Patients with Diffuse Atherosclerosis - Galante, Alberto; Pietroiusti, Antonio; Magrini, Andrea; Carta, Sandro; Franceschelli, Laura; Piccolo, Paola; Pistolese, Giuseppe Raimondo; Martelli, Eugenio; Mastino, Antonio; Matteucci, Claudia; Grelli, Sandro; Favalli, Cartesio (Thrombosis and Haemostasis, 1997)
To evaluate whether atherosclerosis may be associated with altered leucocyte rheology, we assessed leucocyte count (by Coulter counter), aggregation (by means of the leukergy test) and expression of adhesion molecules integrin LFA-1 and CD 44 (by means of immunofluorescence staining and flow cytometry) in 9 patients with carotid plus lower limb artery atherosclerosis (group A), 14 patients with carotid atherosclerosis only (group B) and 23 controls without atherosclerosis (group C). The level of LFA-1 (calculated as mean fluorescence channels - MFCs) on neutrophils, lymphocytes and monocytes was significantly higher (p <0.05) in group A and B patients than in controls (group A - mean ± SE : 383.77 ± 9.42 vs 295.45 ± 5.76; 474.22 ± 8.86 vs ± 7.84; 457.66 ± 12.03 vs 396.25 ± 4.37. Group B: 322.42 ± 6.36 vs 295.45 ± 5.76; 421.42 ± 7.21 vs 388.35 ± 7.84; 415.71 ± 7.73 vs 396.25 ± 4.37, respectively); furthermore, the MFC of LFA-1 on neutrophils was significantly different (p <0.05) between group A and B patients. The percentage of aggregated leucocytes was significantly higher (p <0.05) in group A patients (4.46 ± 1.07) than those in groups B (1.75 ± 0.38) and C (1.43 ± 0.25), whereas no significant difference was detected between groups B and C. Leucocyte number and expression of CD44 were not significantly different among the 3 groups. In conclusion, changes in leucocyte rheology are present in patients with atherosclerosis and may contribute to chronic ischaemia.